PENERAPAN AUDIT MANAJEMEN UNTUK MENILAI KINERJA KARYAWAN BAGIAN PEMASARAN - Hudaifi, Hudaifi; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purposes of this research are (1) to find out the implementation of management audit in order to examine theemployeesâ performance specifically in the marketing department, and (2) to analyze some factors that canincrease the marketing performance. The scope of this research is the staffs on PT. Sinar Mas Trasindo Surabayaparticularly on the human resources management department (MSDM). The data analysis technique has beencarried out by performing observation, interview, and documentation which is related to the management auditto assess the human resources performance on PT. Sinar Mas Trasindo Surabaya. The result of the researchshows that the problem which has been encountered by PT. Sinar Mas Trasindo Surabaya is the performance ofthe Human Resources Management department which is less maximal in the recruitment process since theHuman Resources Management department cannot meet the target which has been determined by the company.The Human Resources Management department cannot use the recruitment cost efficiently so the target cannotbe fulfilled yet. Moreover, there is no career promotion if the employees cannot reach the target, so that theemployees are not encouraged to reach their target. In associated with the audit management which is meant toassess the performance of the employees of marketing department, it has been expected that the management ofthe company can analyze and make some policies can lead to the improvement. So the audit management can beused to assess the performance of the employees of marketing department and the result of the assessment can beused as the control instrument of marketing department. So it can reach efficiency, effectiveness and economicalsince marketing is the most important key in reaching the realization target of the company.Keywords: Audit Management, Human Resources Management, Marketing, Recruitment.